2017
DOI: 10.1037/xhp0000347
|View full text |Cite
|
Sign up to set email alerts
|

Gaze control during interceptive actions with different spatiotemporal demands.

Abstract: It is widely accepted that the sources of information used to guide interceptive actions depend on conflicting spatiotemporal task demands. However, there is a paucity of evidence that shows how information pick-up during interceptive actions is adapted to such conflicting constraints. The present study therefore examined the effects of systematic manipulations of spatiotemporal constraints on performance, timing and gaze in an in situ interceptive action. To this end, expert futsal goalkeepers faced penalty k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…Moreover, the low predictive value of the kinematics of the kicks with respect to height seems to make the use of trajectory information the better option. Consistent with the previous findings, Navia et al (2017) showed that for 6 and 10 meters futsal penalty kicks the average start of hand movements toward the ball trajectory started 188 and 212 ms after ball contact respectively. These results allow the possibility of guiding the hands toward the vertical direction of the ball using ball trajectory information.…”
Section: Timing Of the Saving Actionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the low predictive value of the kinematics of the kicks with respect to height seems to make the use of trajectory information the better option. Consistent with the previous findings, Navia et al (2017) showed that for 6 and 10 meters futsal penalty kicks the average start of hand movements toward the ball trajectory started 188 and 212 ms after ball contact respectively. These results allow the possibility of guiding the hands toward the vertical direction of the ball using ball trajectory information.…”
Section: Timing Of the Saving Actionsupporting
confidence: 91%
“…Less is known about the gaze behavior during the ball flight. Although they considered a different sport, for the ball flight phase it is tempting to consider the above-mentioned study on futsal by Navia et al (2017). These authors showed that, for 6 and 10 m penalty kicks, during the run-up futsal goalkeepers frequently fixate the body of the penalty taker.…”
Section: Gaze Direction and Information Usagementioning
confidence: 99%
“…Notably, the goalkeepers tended to start after the required time exceeded the available time (i. e., they waited too long, that is, until after required velocity had exceeded maximum velocity). Still, the two goalkeepers who made the most saves were closest to their action boundary, although not all proficient goalkeepers acted close to their action boundary (see also Navia et al, 2017). This suggests that these goalkeepers were not optimally calibrated.…”
Section: Affordance-based Control In Goalkeeping In the Penalty Kick:mentioning
confidence: 98%
“…However, this early information is less adaptive, and the longer before ball-contact, the more loosely it is coupled to the resulting ball trajectory (Franks & Harvey, 1997;Diaz, Fajen, & Phillips, 2012;Lopes, Jacobs, Travieso, & Araújo, 2014). This presents goalkeepers with conflicting requirements (Navia, Dicks, van der Kamp, & Ruiz, 2017). They may wait long to exploit the specifying information from ball-flight.…”
Section: The Leading Approach: Saving Penalty Kicks Is a Perceptual Smentioning
confidence: 99%
See 1 more Smart Citation